Analysis slope stability based on physical properties in Cepoko Village, Indonesia. Issue 1 (1st January 2021) - Setyawan, Agus; Alina, Ana; Suprapto, Dwiyanto; Gernowo, Rahmat; Suseno, Jatmiko E.; Hadiyanto, H.
Abstract: Semarang is one of the industrial cities that continues to experience developments that eventually force peri-urban areas such as Gunungpati District to be converted into residential areas. Cepoko is one of the subdistricts in Gunungpati District that has developed into a subservice center along with the development of settlements in this district. The fact that Cepoko is in a sloping area and many landslides that have occurred make the risk of landslides become the reason for the importance of slope stability analysis. Grouting is a soil strengthening method to increase soil particle bonding so that it can be a solution for landslide prevention in sloping areas. The purpose of this study is analyzing the slope stability and simulating the grouting method. This study takes secondary data such as core drilling data, geoelectric data, and laboratory test data (index properties test, direct shear test, and uniaxial compressive test) obtained from Selimut Bumi Adhi Cipta Inc. The slope stability analysis is one of the methods to interpret field subsurface structure using index properties test, direct shear test, and uniaxial compressive test by software of rocscience slide 6.0. After interpreting field subsurface structure then grouting simulation applied into software to compare initial slope stability and after applying grouting. The results of the slope stability analysis showed that the initial slope had a safety factor of 0.847, indicating that the potential for landslides often occurred. The grouting simulation was carried out by changing the cohesion six times, strongly influencing the increase in the safety factor to 1.294, indicating a relatively stable slope.